PENGARUH SISTEM INFORMASI SUMBER DAYA MANUSIA DAN KINERJA KARYAWAN TERHADAP EFEKTIVITAS ORGANISASI : (Studi Pada Koperasi Simpan Pinjam Bhina Raharja) - Haris Fauzi; Engkun Kurnadi; Helma Herawati (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
An employee's work productivity and work efficiency are not in perfect harmony. This is due tothe sub-optimal implementation of personal information systems and the staff performance of Bhina Raharja Savings and Loan Cooperative. The purpose of this study is to investigate theim pactof HR information systems and employee performance on the organizational performance of Bhina Raharja employees. Thetypeofre searchis descriptive and very fiable through survey methods. The main population of this study was the employees of Bhina a The sampling technique used is saturated sampling technique. The data collection technique for this study was a questionnaire using a Likert scale. The analytical tool of this study is multiple linear regression analysis, coefficient determination analysis, which was previously conducted as a classical hypothesis test and then tested the hypothesis. The results show edthat the person information system and personnel performance hada positive and significante ffecton organizational efficiency both partially and simultan eously.